Disturbed Mental Imagery of Affected Body-Parts in Patients with Hysterical Conversion Paraplegia Correlates with Pathological Limbic Activity - Saj, Arnaud (MDPI, 2014)
Patients with conversion disorder generally suffer from a severe neurological deficit which cannot be attributed to a structural neurological damage. In two patients with acute conversion paraplegia, investigation with functional magnetic resonance imaging (fMRI) showed that the insular cortex, a limbic-related cortex involved in body-representation and subjective emotional experience, was activated not only during attempt to move the paralytic body-parts, but also during mental imagery of their movements. In addition, mental rotation of affected body-parts was found to be disturbed, as compared to unaffected body parts or external objects. fMRI during mental rotation of the paralytic body-part showed an activation of another limbic related region, the anterior cingulate cortex. These data suggest that conversion paraplegia is associated with pathological activity in limbic structures involved in body representation and a deficit in mental processing of the affected body-parts.